(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
The influence of vitamins Bc (folic acid, FA), B1 (thiamine, TA) and C (ascorbic acid, AA) on H2O2 (HP) decomposition rate in aqueous solutions was studied using gasometric method. In alkaline medium in the presence of FA the reactions are carried out at [H2O2]0=[HOO–]=0.5 M. [FA]0 is changed in the range 0–2.8∙10–3 M. It is established that the reaction rate (W) decreases more than twofold. It is assumed that FA effectively reacts with HO• and HOO•, which are chain carriers. So the reaction runs by radical-chain mechanism. In acidic medium (pH 3.5) catalyzed by Fe(II) cations HP decomposition occurs mainly by radicalchain mechanism. TA (0–2.5∙10–4 M) also decreases W more than 4 times. At pH 3.5, [TA∙HCl]0 ≥ 1∙10–4 M there is no O2 evolution. The AA influence on the HP decomposition, W is studied at pH 3.5. In the presence of AA, [AA]0≈1.25∙10–3 M, W also decreases the radical-chain run catalyzed by Fe(II) cations HP decomposition.